ILDIZ VA UNING VAZIFASI, ILDIZNING TURLARI. BIRLAMCHI VA IKKILAMCHI ANATOMIK TUZILISHI (Ta'limning zamonaviy transformatsiyasi, 2024)
Annatation.This thesis describes in detail the morphological and anatomical structure, functions and types of plant roots. Information is provided on the primary and secondary anatomical structure of the root.Анатомия.В данной диссертации подробно описывается морфологическое и анатомическое строение, функции и типы корней растений. Представлена информация о первичном и вторичном анатомическом строении корня.